Adequacy of setting standards for kick impact in the Taekwondo electronic scoring system: comparison of a reference group model based on empirical data - Chang-Hwan Choi; Hyeri Oh; Minsoo Jeon (BMC, 2021)
Abstract Background In Taekwondo competitions, the rule is that points are scored when the impact of the kick reaches a predetermined threshold of strength. This study aimed to explore the adequacy of the protector and scoring system (PSS) designed to determine taekwondo body scoring based on a reference group model (RGM). Specifically, the kicking impact of the PSS was calculated using data from 188 matches fought during of 2018 Jakarta Asian Games. The RGM was designed based on empirical data by classifying the victory and defeat groups by gender and weight class, and the scoring method was set according to these criteria. Result The result of this study are as follows. First, there was no difference in the average impact of kicks of taekwondo players by weight class. Second, result of setting up the kick scoring impact standards of taekwondo PSS by classifying the winning and non-winning groups, the kick scoring impact set by the WT was found to be high in all weight classes except 58 kg. Lastly, result of comparing the settings of impact to score according to weight classes, the kick scoring impact standard set by the WT was higher in heavyweight (men's: under 80 kg, + 80 kg, women's: under 67 kg, over 67 kg) than in the lightweight (men's: under 58 kg, under 63 kg, under 68 kg, women's: under 49 kg, under 53 kg, under 57 kg). Conclusion The kick scoring impact set by the WT was found to be high in all weight classes except for the under 58 kg class defining kick scoring impact based on the standards of WT-certified PSS by classifying the matches into winning and non-winning groups. Finally, as a result of comparing the scoring impact settings according to weight class, the kick scoring impact standard set by the WT was higher for the heavier weight classes than for the lighter weight classes.